My Employer’s Prestige, My Prestige - Sander, Tom; Teh, Phoey Lee * (Springer, 2019)
Employer branding is an essential component that attracts potential candidates to companies. Social media, particularly employer rating platforms, provide many opportunities to present a company’s employer brand. Individuals use these platforms to collect information and evaluations about potential employers and companies could utilise these platforms to present themselves favourably. Based on social capital theory, this study examined the variables of support and benefit as reasons why individuals share information about their employers on employer rating platforms. The influence of demographic factors on the use of these platforms was also investigated. Data was collected from 309 respondents via an online survey, and analysed using the t-test, Spearman’s correlation, and analysis of variance (ANOVA) with the least significant difference (LSD) method. Only descriptive statistics, distribution of responses, and statistically significant results are presented.